Heat Stress Affects Jejunal Immunity of Yellow-Feathered Broilers and Is Potentially Mediated by the Microbiome - Liu, Wen-Chao; Huang, Meng-Yi; Balasubramanian, Balamuralikrishnan; Jha, Rajesh (Frontiers in Physiology, 2022)
In the perspective of the global climate change leading to increasing temperature, heat stress (HS) has become a severe issue in broiler production, including the indigenous yellow-feathered broilers. The present study aimed to investigate the effects of HS on jejunal immune response, microbiota structure and their correlation in yellow-feathered broilers. A total of forty female broilers (56-day-old) were randomly and equally divided into normal treatment group (NT group, 21.3 ± 1.2 °C, 24 h/day) and HS group (32.5 ± 1.4 °C, 8 h/day) with five replicates of each for 4 weeks feeding trial. The results showed that HS exposure increased the contents of TNF-α, IL-1β, and IL-6 in jejunal mucosa (P < 0.05). The HS exposure up-regulated the relative fold changes of NF-κB, TNF-α, IL-1β, and IL-6 (P < 0.01) while down-regulated the relative fold change of IFN-γ in jejunal mucosa (P < 0.05). Meanwhile, HS had no significant impacts on alpha diversity of jejunal microbiota such as Simpson, Chao1 richness estimator (Chao 1), abundance-based coverage estimators (ACE), and Shannon index (P > 0.10). Broilers exposed to HS reduced the jejunal microbial species number at the class and order level (P < 0.05). Moreover, HS decreased the relative abundance of Ruminococcus, Bdellovibrio, and Serratia at the genus level in jejunum (P < 0.05). At the phylum level, four species of bacteria (Bacteroidetes, Cyanobacteria, Thermi, and TM7) were significantly associated with immune-related genes expression (P < 0.05). At the genus level, ten species of bacteria were significantly correlated with the expression of immune-related genes (P < 0.05), including Caulobacteraceae, Actinomyces, Ruminococcaceae, Thermus, Bdellovibrio, Clostridiales, Sediminibacterium, Bacteroides, Sphingomonadales and Ruminococcus. In particular, the microbial with significantly different abundances, Ruminococcus and Bdellovibrio, were negatively associated with pro-inflammatory cytokines expression (P < 0.05). These findings demonstrated that HS exposure promoted the production of pro-inflammatory cytokines in yellow-feathered broilers’ jejunum. The detrimental effects of HS on jejunal immune response might be related to dysbiosis, especially the reduced levels of Ruminococcus and Bdellovibrio.